Adult neural precursor cells unaffected in animal models of DYT1 dystonia - Regensburger, Martin; Kohl, Zacharias; Grundmann, Kathrin; Winner, Beate; Riess, Olaf; Winkler, Jürgen (NeuroReport, 2009)
Hereditary dystonias in humans are frequently related to a specific mutation of the DYT1 gene that encodes torsinA. This mutation has been shown to disrupt neuronal cell migration during development. We compared adult neurogenesis, occurring in the hippocampus and the olfactory bulb, in transgenic mice overexpressing either the wild-type or mutant form of human torsinA. Neurogenesis was assessed by quantification of bromodeoxyuridine-labeled cells. Both transgenic mouse models displayed perinuclear inclusions in the brainstem and in mitral cells of the olfactory bulb, altered striatal dopamine levels, and behavioral abnormalities. However, both hippocampal and olfactory neurogenesis levels were unchanged compared with control animals. We conclude that overexpression of human wild-type or mutant torsinA does not affect the survival of adult newborn neurons. © 2009 Wolters Kluwer Health | Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2021-08-17
Keywords: Bromodeoxyuridine; Cellular plasticity; Doublecortin; Dystonia; DYT1; Hippocampus; Olfactory bulb; Subventricular zone; TorsinA